A subsistência pela fé: a interferência presbiteriana na formação política, econômica e social da cidade de Várzea Nova - BA - Rios, Eduardo Dias (2015)
This study investigated the incursion of the Presbyterian Church in Brazil, the Calvinist ethics course and to establishment in the city of Várzea Nova-BA. The research sought within a theoretical perspective, scrutinize the direction of Presbyterianism in Brazil and, above all, as this was fundamental to the establishment and consolidation of the city of Várzea Nova - BA. It was from this religious perspective that the city of Várzea Nova can an alternative livelihood, namely the sisalana agave (sisal) that will be essential culture, and economic base for its development and subsistence factor for the local population. Associated with the Catholic faith, already present in the regional scenario, Presbyterianism, by Rev. Otacílio Alcantara, begins his journey, and based in a Puritan ethic of vocation, creates the mechanisms for formation of the community, supporting the economic formation of the local genesis. The whole analysis is theoretical basis Weberian sociology, in addition to long-term narratives that built the memory of varzeanovense people and formed the structure needed for the construction of this work.